Bee community as a source of energy in the production of food, honey-plants in the ecosystem of Croatian forests’ hunting grounds - Tucak, Zvonimir (Array, 2009)
Summary: In addition to the process of photosynthesis, the bee community is the main source of energy in food production, honey-plants used by game and people in the hunting grounds ecosystem. It is a well-known fact that thousands of plant species depend on the presence of bee communities (pollination, fertilization). In this paper we studied the presence of the bee community in the hunting grounds of Croatian Forests, and their influence on the number of game (wild pigs), as well as the quality of honey, honey plants in the hunting grounds used by people and game. We established the total number of game (wild boars). The honey quality parameters were determined using the Harmonised methods of the European Honey (Bogdanov et al., 1997) and the pollen analysis by were conducted according to Harmonised methods of melissopalynology (Von der Ohe et al., 2004). Research results indicate that the presence of the bee community influences the number of wild boars from 3–18%, and the quality of honey is in line with the European and world standards. The SAS/STAT package was used for the statistical analysis (SAS Institute Inc., 2000). The significance of the differences among the groups was determined by Duncan test